Pengaruh Model Pembelajaran Experiential Learning Berbantuan Media Wordwall terhadap Hasil Belajar Siswa Kelas IV Sekolah Dasar - Emia Latersia S. Berahmana; Patri Janson Silaban; Lasmaria Agnes Sinaga; Darinda Sofia Tanjung; Antonius Remigius Abi (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aimed to determine the effect of the Experiential Learning model assisted by Wordwall media on the science and social studies (IPAS) learning outcomes of fourth-grade students at UPT SD Negeri 064990 Medan Johor on the topic Me and My Needs. This research employed a quantitative approach using a One Group Pretest-Posttest Design. The sample consisted of 30 students selected through total sampling. The research instruments included a learning achievement test and a student response questionnaire that had met validity and reliability requirements. Data were analyzed using descriptive and inferential statistics, including normality tests, Pearson Product Moment correlation, coefficient of determination, and t-test. The findings showed that the mean pretest score increased from 47.50 to 84.33 on the posttest. The correlation coefficient was 0.632, indicating a strong relationship, while the hypothesis test produced a significance value of 0.000 (< 0.05). Therefore, the Experiential Learning model assisted by Wordwall media significantly improved students' IPAS learning outcomes and is recommended as an effective learning innovation to support the implementation of the Merdeka Curriculum in elementary schools.